Ovarian cancer: ion channel and aquaporin expression as novel targets of clinical potential - Frede, Julia; Fraser, Scott P.; Oskay-Özcelik, Gülten; Hong, Yeosun; Ioana Braicu, E.; Sehouli, Jalid; Gabra, Hani; Djamgoz, Mustafa B. A. (European journal of cancer, 2013)
Ovarian cancer is associated with limited overall survival, due to problems in early detection and therapy. Membrane ion channels have been proposed to play a significant, concerted role in the cancer process, from initial proliferation to metastasis, and promise to be early, functional biomarkers. We review the evidence for ion channel and aquaporin expression and functioning in human ovarian cancer cells and tissues. In vitro, K+ channels, mainly voltage-gated, including Ca2+-activated channels, have been found to control the cell cycle, as in other cancers. Voltage-gated, volume-regulated and intracellular Cl− channels have been detected in vitro and in vivo and shown to be involved in proliferation, adhesion and invasion. Evidence for ‘transient receptor potential’, voltage-gated sodium and calcium channels, which have been shown to contribute to pathogenesis of other carcinomas, is also emerging in ovarian cancer. Aquaporins may be involved in cell growth, migration and formation of ascites via increased water permeability of micro-vessels. It is concluded that functional expression of ion channels and their regulation by steroid hormones and growth factors are an integral part of ovarian cancer development and progression. Furthermore, ion channels may be involved in multidrug resistance, commonly associated with treatment of ovarian cancer. We propose that ion channel studies can facilitate our understanding of the pathobiology of ovarian cancer and, ultimately, can serve as viable novel targets for its clinical management.